The cranial morphology of the fruit-piercing moth, Serrodes partita (Fabr.) with special reference to the feeding mechanism - Swart, Philippus Lodewikus (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D. Agric.) -- University of Stellenbosch, 1969.